Formula and manufacturing method of Zr-containing double-high-series sintered permanent magnet
By adding ZR elements and CU, GA elements to the two-high-tie sintering permanent magnet formula, inhibit the generation of α-FE and enhance the coupling of the soft magnetic phase and the hard magnetic phase The problem of magnetic and highly corrected force realizes high -performance and low -cost dual -high -quality sintering permanent magnets.
Patent Information
- Application Number
- CN202411596549.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to achieve high residual magnetism and high coercivity at the same time, and it is easy to generate an α-Fe phase that is unfavorable to magnetic properties, resulting in unsatisfactory volume fraction of the hard magnetic phase and weak exchange coupling effect between the hard magnetic phase and the soft magnetic phase.
Using a Zr-containing double high-series sintered permanent magnet formula, the Zr element is added to suppress the generation of α-Fe, increase the volume fraction of the hard magnetic phase, and enhance the soft magnetic phase and hard magnetic phase through the Cu-Ga phase formed by Cu and Ga elements. phase exchange coupling.
The double -high sintering permanent magnets that are highly left magnetic and high -powered, which improves the volume scores of the hard magnetic phase and the switching coupling of soft magnetic phase, while reducing the cost.
Smart Images

Figure CN119361277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnets, in particular to a formula and a manufacturing method of a Zr-containing dual-high system sintered permanent magnet. Background Art
[0002] In today's energy and electronics and many other fields, high-performance permanent magnets play an indispensable and key role. With the continuous advancement of science and technology, such as the pursuit of improved generator efficiency in wind power generation, the electric vehicle industry's demand for increased mileage and enhanced power performance, and the trend of electronic equipment towards miniaturization and high performance, all put forward higher and higher requirements on the performance of permanent magnets, especially in application scenarios that require both high remanence and high coercivity.
[0003] However, with current technology, it is difficult to achieve high remanence and high coercivity at the same time. It is easy to generate α-Fe phase which is not conducive to magnetic properties, resulting in unsatisfactory volume fraction of hard magnetic phase and weak exchange coupling between hard magnetic phase and soft magnetic phase. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a formula and a manufacturing method for a Zr-containing dual-high system sintered permanent magnet, which solves the problem that it is difficult to achieve high remanence and high coercivity at the same time, and that an α-Fe phase that is not conducive to magnetic properties is easily generated.
[0005] To achieve the above objectives, the present invention is implemented by the following technical solutions: A Zr-containing dual-high system sintered permanent magnet formula, including the following components: RxT100-xy-zMyBz;
[0006] Wherein, X, Y, and Z are the mass fractions of the corresponding elements, 28.5%≤X≤30.5%, 1%≤Y≤1.5%, and 0.86%≤Z≤0.96%;
[0007] R is selected from one or more of Pr, Nd, Ce, Gd, Ho, Dy and Tb;
[0008] M is Cu, Ga and Zr, and the content of Cu is 0.2%-0.45%, the content of Ga is 0.25%-0.55%, and the content of Zr is 0.3%-0.5%;
[0009] T is Co and Fe, wherein 0.3%≤Co≤1.5%Co, and the remainder is Fe and impurities in the raw materials.
[0010] Preferably, the content of Pr in the R is 6%-8%, the content of Nd is 22%-23.5%, the content of Dy is 0-1%, and the content of Tb is 0-0.6%.
[0011] Preferably, the Cu content in the M is 0.25%-0.45%, the Ga content is 0.35%-0.55%, the Zr content is 0.3%-0.5%, the Al content is 0.03%-0.2%, the Co content in the T is 0.3%-1.5%, and the B content is 0.88%-0.93%.
[0012] Preferably, the RxT100-xy-zMyBz includes PrNd 29%-30.5%, Co 0.5%, Cu 0.2%-0.45%, Ga 0.3%-0.55%, Zr 0.3%-0.5%, B 0.91%, Al 0.05% and the balance is Fe and impurities in the raw materials.
[0013] A method for manufacturing a Zr-containing dual-high system sintered permanent magnet comprises the following steps:
[0014] S1. Vacuum melting and hydrogen crushing: using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of the remaining formula, a vacuum melting furnace is used to make alloy flakes, and then the alloy flakes are subjected to hydrogen crushing treatment;
[0015] S2, air jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen;
[0016] S3, orientation molding: Orientation molding is carried out in an orientation magnetic field when the oxygen content of the press is lower than 500ppm, and then vacuum packaging and cold isostatic pressing are carried out to achieve a densification effect;
[0017] S4, vacuum sintering: placing the green body after cold isostatic pressing in a vacuum sintering furnace, and performing gradient sintering after vacuuming;
[0018] S5, grain boundary diffusion and aging treatment: the sintered blank is made into a 30*30*5mm square piece and then subjected to grain boundary diffusion treatment, and then to aging treatment;
[0019] S6. Performance test: The aging treated blank is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0020] Preferably, the treatment temperature of the alloy sheet in S1 is within 1500°C, the thickness is 0.1-0.5 mm, the dehydrogenation temperature in the hydrogen cracking treatment is 520-580°C, and the hydrogen content of the coarse powder after dehydrogenation is 600-1500 ppm.
[0021] Preferably, the proportion of organic additives in S2 is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5 hours, the online particle size of the jet mill is D50: 3.8-4.3 μm, and the system oxygen supplementation is 30 ppm.
[0022] Preferably, the intensity of the orientation magnetic field in S3 is greater than 1.6 T, and in the cold isostatic pressing treatment, the pressure is 160-220 MPa, and the holding time is 15-35 s.
[0023] Preferably, the sintering temperature of the vacuum sintering in S4 is 1020-1120°C, the high temperature holding time is 4-12h, the vacuum degree is ≤0.5Pa, the aging treatment is multi-stage aging, including primary aging, secondary aging, and tertiary aging, the primary aging treatment temperature is 850°C-950°C, the holding time is 1-3h, the secondary aging treatment temperature is 420°C-520°C, the holding time is 3-10h, the tertiary aging treatment temperature is 550°C-650°C, the holding time is 3-10h, and the density of the sintered blank is >7.5.
[0024] Preferably, the diffusion source in the grain boundary diffusion in S5 includes terbium hydride, dysprosium hydride, terbium alloy, dysprosium alloy, the grain boundary diffusion process includes one of screen printing, coating and PVD, the grain boundary diffusion temperature is 820°C-920°C, and the diffusion time is 10-30h.
[0025] The invention provides a formula and a manufacturing method of a Zr-containing dual-high system sintered permanent magnet.
[0026] It has the following beneficial effects:
[0027] 1. The present invention suppresses the generation of α-Fe by adding non-rare earth element Zr, increases the volume fraction of hard magnetic phase, enhances the delivery coupling effect with soft magnetic phase, and refines the grains. The Cu-Ga phase formed by Cu and Ga elements in the alloy suppresses the R2T17 phase and generates more R-Cu-Ga phase as the Zr content increases, so that a dual high system sintered permanent magnet with high remanence and high coercivity can be obtained.
[0028] 2. The Cu-Ga phase in the present invention utilizes its low melting point and wettability between grain boundaries to enhance the flow continuity between grain boundaries, thereby enhancing the diffusion depth of the grain boundary diffusion process and improving the demagnetization resistance of the sintered permanent magnet.
[0029] 3. The cost of the Zr-containing dual-high system sintered permanent magnet of the present invention is much lower than the same type of sintered permanent magnet on the market. The blank performance is Br≥14.55KGs, Hcj≥16koe, and the grain boundary diffusion (<0.5Tb) is Br≥14.4KGs, Hcj≥26koe. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of a method for manufacturing a Zr-containing dual-high system sintered permanent magnet. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Please see attached Figure 1 , the embodiment of the present invention provides a formula of a double high system sintered permanent magnet containing Zr, comprising the following components: RxT100-xy-zMyBz;
[0033] Wherein, X, Y, and Z are the mass fractions of the corresponding elements, 28.5%≤X≤30.5%, 1%≤Y≤1.5%, and 0.86%≤Z≤0.96%;
[0034] R is selected from one or more of Pr, Nd, Ce, Gd, Ho, Dy and Tb;
[0035] M is Cu, Ga and Zr, and the content of Cu is 0.2%-0.45%, the content of Ga is 0.25%-0.55%, and the content of Zr is 0.3%-0.5%;
[0036] T is Co and Fe, wherein 0.3%≤Co≤1.5%Co, and the remainder is Fe and impurities in the raw materials.
[0037] The content of Pr in R is 6%-8%, the content of Nd is 22%-23.5%, the content of Dy is 0-1%, and the content of Tb is 0-0.6%.
[0038] The Cu content in M is 0.25%-0.45%, the Ga content is 0.35%-0.55%, the Zr content is 0.3%-0.5%, the Al content is 0.03-0.2%, the Co content in T is 0.3%-1.5%, and the B content is 0.88%-0.93%.
[0039] RxT100-xy-zMyBz includes PrNd 29%-30.5%, Co 0.5%, Cu 0.2%-0.45%, Ga 0.3%-0.55%, Zr 0.3%-0.5%, B 0.91%, Al 0.05% and the balance is Fe and impurities in the raw materials.
[0040] Specifically, among the elements R, rare earth elements such as Pr and Nd have large atomic magnetic moments. In the microstructure of the permanent magnet, the exchange interaction formed between them and transition metal elements such as Fe and Co is conducive to the orderly arrangement of the magnetic moments, thereby improving the remanence of the permanent magnet. At the same time, the addition of heavy rare earth elements such as Dy and Tb can significantly improve the coercive force of the permanent magnet. By selecting one or more of Pr, Nd, Ce, Gd, Ho, Dy and Tb as the R element, the coercive force can be flexibly adjusted according to specific application requirements.
[0041] In the element M, the content of Cu element is between 0.2% and 0.45%. During the sintering process, Cu element hinders the growth of grains by segregation at the grain boundary, so that the permanent magnet obtains a better microstructure, and at the same time helps to maintain the relative stability of magnetic properties and reduce the decline of magnetic properties caused by temperature fluctuations. The main role of Ga is to change the electronic structure and magnetic interaction of the permanent magnet, so that the permanent magnet can still maintain good magnetism in a high temperature environment, broaden the application temperature range of the permanent magnet, and at the same time improve the microstructure and promote the uniform distribution of elements. Zr element is a non-rare earth element, which inhibits the formation of α-Fe, increases the volume fraction of the hard magnetic phase, and enhances the delivery coupling effect with the soft magnetic phase. At the same time, it can also refine the grains. The Cu-Ga phase formed by Cu and Ga elements in the alloy, as the Zr content increases, suppresses the R2T17 phase and generates more R-Cu-Ga phases, so that a dual high system sintered permanent magnet with high remanence and high coercivity can be obtained;
[0042] Among the elements T, Fe, as the main transition metal element, is the key medium of magnetic exchange in permanent magnets. The 3d electrons of Fe atoms participate in the formation of strong magnetic interactions, and together with rare earth elements and other added elements, they construct the magnetic structure of permanent magnets. In the formula, the balance is Fe and impurities, which means that Fe accounts for a large proportion of the entire composition and is an important basis for maintaining the basic magnetism of permanent magnets. The addition of Co can improve the magnetocrystalline anisotropy of permanent magnets and make the arrangement of magnetic moments in the crystal more stable. At the same time, there is a synergistic effect between Co and Fe, which can optimize the internal magnetic structure of permanent magnets and further improve the magnetic properties of permanent magnets. The Co element can also improve the corrosion resistance of permanent magnets to a certain extent and extend the service life of permanent magnets in practical applications.
[0043] A method for manufacturing a Zr-containing dual-high system sintered permanent magnet comprises the following steps:
[0044] S1. Vacuum melting and hydrogen crushing: using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of the remaining formula, a vacuum melting furnace is used to make alloy flakes, and then the alloy flakes are subjected to hydrogen crushing treatment;
[0045] S2, air jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen;
[0046] S3, orientation molding: Orientation molding is carried out in an orientation magnetic field when the oxygen content of the press is lower than 500ppm, and then vacuum packaging and cold isostatic pressing are carried out to achieve a densification effect;
[0047] S4, vacuum sintering: placing the green body after cold isostatic pressing in a vacuum sintering furnace, and performing gradient sintering after vacuuming;
[0048] S5, grain boundary diffusion and aging treatment: the sintered blank is made into a 30*30*5mm square piece and then subjected to grain boundary diffusion treatment, and then to aging treatment;
[0049] S6. Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0050] Specifically, the vacuum melting furnace in S1 can fuse a variety of metal raw materials together under high temperature and vacuum environment to produce alloying reaction, ensure that all elements can be fully mixed, and realize uniform distribution of the entire alloy composition. At the same time, on the one hand, some volatile impurity elements will evaporate under vacuum and high temperature conditions, thereby reducing the impurity content. On the other hand, the vacuum environment can prevent oxygen, nitrogen and other gases in the air from mixing into the alloy, avoiding the formation of impurity phases such as oxides and nitrides. Hydrogen crushing is an effective grain refinement method, which can make the alloy easier to break into fine particles in the subsequent processing process, thereby optimizing the microstructure of the permanent magnet and improving the magnetic properties.
[0051] The friction between the raw material particles in S2 and between the particles and the wall of the grinding equipment will generate a lot of heat and may cause the particles to agglomerate. The organic additives can form a thin film on the surface of the particles to reduce friction and reduce the possibility of particle agglomeration, making the grinding process smoother and conducive to obtaining stable magnetic properties. After the antioxidant is added to the ground powder, a protective film will be formed on the surface of the powder particles to prevent the oxide from having a negative impact on the magnetic properties of the permanent magnet. The nitrogen filling storage is based on the formation of a protective film by the antioxidant, and further creates a low-oxygen environment to reduce the chance of oxygen contact with the powder;
[0052] In S3, under the action of the orientation magnetic field, the magnetic particles in the permanent magnet powder will rotate, so that their easy magnetization direction tends to be consistent with the magnetic field direction, ensuring the consistency of the magnetic domain orientation inside the entire permanent magnet. Orientation molding in a low-oxygen environment (the oxygen content of the press is less than 500ppm) can effectively prevent the permanent magnet powder from being oxidized during the pressing process, thereby ensuring the high quality of the permanent magnet. The subsequent cold isostatic pressing applies uniform pressure to the vacuum-encapsulated permanent magnet to reduce the gaps between the powder particles, thereby increasing the density of the permanent magnet and improving the microstructure of the permanent magnet.
[0053] In the vacuum sintering process of S4, the vacuum operation can discharge the oxygen and other oxidizing gases in the furnace, which can effectively prevent the contact between oxygen and metal elements and prevent the occurrence of oxidation reaction. Gradient sintering is a process that gradually changes the sintering temperature. The gradual temperature increase method can more accurately control the growth rate of the grains.
[0054] In S5, the blank is made into square pieces of specific size, so that the subsequent processes such as grain boundary diffusion treatment and aging treatment can be carried out more standardized. In the sintered permanent magnet, the grain boundary has an important influence on the magnetic properties. The diffusion elements usually react with other elements at the grain boundary to form new compounds or phases, which can make the grain boundary clearer, continuous and stable. During the aging treatment, precipitation reactions of elements will occur inside the permanent magnet. Through aging treatment, the microstructure of the permanent magnet can be optimized without destroying the overall stability.
[0055] In S6, the aging-treated blank is made into a D1010 sample column in order to match the test fixture and test principle of the NIM-62000 permanent magnetic performance tester to ensure the accuracy of the test data. At the same time, the NIM-62000 permanent magnetic performance tester can comprehensively evaluate the key performance indicators of the permanent magnet to determine whether the product quality and performance meet the standards.
[0056] The processing temperature of the alloy sheet in S1 is within 1500°C, the thickness is 0.1-0.5mm, the dehydrogenation temperature in the hydrogen cracking treatment is 520-580°C, and the hydrogen content of the coarse powder after dehydrogenation is 600-1500ppm.
[0057] The proportion of organic additives in S2 is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygen supplementation is 30ppm.
[0058] The orientation magnetic field strength in S3 is greater than 1.6 T. During the cold isostatic pressing treatment, the pressure is 160-220 MPa and the holding time is 15-35 s.
[0059] The sintering temperature of vacuum sintering in S4 is 1020-1120℃, the high temperature holding time is 4-12h, the vacuum degree is ≤0.5Pa, and the aging treatment is multi-stage aging, including primary aging, secondary aging, and tertiary aging. The primary aging treatment temperature is 850℃-950℃, and the holding time is 1-3h. The secondary aging treatment temperature is 420℃-520℃, and the holding time is 3-10h. The tertiary aging treatment temperature is 550℃-650℃, and the holding time is 3-10h. The density of the sintered blank is >7.5.
[0060] The diffusion sources in the grain boundary diffusion in S5 include terbium hydride, dysprosium hydride, terbium alloy, and dysprosium alloy. The grain boundary diffusion process includes one of screen printing, coating, and PVD. The grain boundary diffusion temperature is 820° C.-920° C., and the diffusion time is 10-30 hours.
[0061] Embodiment 1
[0062] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the composition is designed according to PrNd29%, B0.91%, Cu0.2%, Co0.5%, Zr0.3%, Nb0.3%, Ga0.3% and Fe balance, and the alloy sheets are made in a vacuum melting furnace. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1, and the appearance is silvery white.
[0063] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0064] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0065] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0066] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0067] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0068] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0069] Embodiment 2
[0070] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the alloy is made into sheets in a vacuum melting furnace according to the composition design of PrNd29.3%, B0.91%, Cu0.25%, Co0.5%, Zr0.35%, Nb0.3%, Ga0.35% and Fe balance. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1mm, and the appearance is silvery white.
[0071] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0072] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0073] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0074] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0075] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0076] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0077] Embodiment 3
[0078] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the alloy sheets are made in a vacuum melting furnace according to the composition design of PrNd29.6%, B0.91%, Cu0.3%, Co0.5%, Zr0.4%, Nb0.3%, Ga0.4% and Fe balance. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1mm, and the appearance is silvery white.
[0079] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0080] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0081] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0082] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0083] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0084] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0085] Embodiment 4
[0086] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the alloy is made into sheets in a vacuum melting furnace according to the composition design of PrNd29.9%, B0.91%, Cu0.35%, Co0.5%, Zr0.45%, Nb0.3%, Ga0.45% and Fe balance. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1mm, and the appearance is silvery white.
[0087] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0088] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0089] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0090] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0091] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0092] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0093] Embodiment 5
[0094] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the composition is designed according to PrNd30.3%, B0.91%, Cu0.4%, Co0.5%, Zr0.45%, Nb0.3%, Ga0.5% and Fe balance, and the alloy sheets are made in a vacuum melting furnace. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1mm, and the appearance is silvery white.
[0095] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0096] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0097] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0098] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0099] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0100] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0101] Embodiment 6
[0102] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the alloy is made into sheets in a vacuum melting furnace according to the composition design of PrNd30.5%, B0.91%, Cu0.45%, Co0.5%, Zr0.5%, Nb0.3%, Ga0.55% and Fe balance. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1mm, and the appearance is silvery white.
[0103] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0104] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0105] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0106] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0107] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0108] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0109] Comparative Example
[0110] S1: Smelting: Using metal praseodymium and neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, the composition is designed according to PrNd29-30.5%, B0.91%, Cu0.15%, Co0.5%, Zr0.2%, Nb0.3%, Ga0.15% and Fe balance, and the alloy sheet is made into alloy sheet in a vacuum melting furnace. The processing temperature of the alloy sheet is about 1450℃, the thickness is 0.1, and the appearance is silvery white.
[0111] S2: Hydrogen cracking: The alloy sheet is subjected to hydrogen cracking treatment, the dehydrogenation temperature is 520°C, and the hydrogen content of the coarse powder after dehydrogenation is 600ppm;
[0112] S3: Jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen, wherein the proportion of organic additives is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5h, the online particle size of the jet mill is D50: 3.8-4.3μm, and the system oxygenates 30ppm.
[0113] S4: Molding: Orientation magnetic field strength> 1.6T, orientation molding is carried out when the oxygen content of the press is less than 500ppm, and then vacuum packaging is carried out and cold isostatic pressing is carried out to achieve densification effect, and the isostatic pressing pressure is 200MPa.
[0114] S5: Sintering: Place the green body after cold isostatic pressing in a vacuum sintering furnace, evacuate to less than 1 Pa and then perform gradient sintering. The sintering temperature is 1080°C and the high temperature holding time is 6 hours.
[0115] S6: Aging treatment: The sintered blank is subjected to aging treatment, wherein the primary aging temperature is 890°C, and the temperature is kept for 3 hours, and the secondary aging temperature is 470°C, and the temperature is kept for 8 hours;
[0116] S7: Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
[0117] Table (1) shows the formula (wt%) and corresponding magnetic properties (CGS) of dual high-grade sintered permanent magnets.
[0118]
[0119]
[0120] It can be seen from the examples and comparative examples in Table (1) that, under the same total rare earth content, when the different contents of Zr, Cu and Ga are increased, Br does not change much, but Hcj is increased by 1.2-2KOe. Example 3 is preferred in the present invention.
[0121] The sintered blanks in Example 3 and Comparative Example 3 were respectively made into square pieces with a length and width of 20 mm and thicknesses of 3 mm, 5 mm, 8 mm, and 10 mm.
[0122] The thickness direction is the magnetization direction. After surface treatment (which can be sandblasting, pickling and other treatment methods), a raw material mainly composed of terbium hydride is evenly sprayed onto the magnetized surface, and the weight gain on both sides is 0.48% Tb. After high-temperature tunnel drying, the product is packed in a box and vacuum sintered. Diffusion sintering is performed at a temperature of 850°C-920°C, preferably 870°C, and then cooled to 50°C after being kept warm for 15 hours for aging treatment. The temperature is preferably 480°C, and then cooled to 40°C after being kept warm for 6 hours before being taken out of the furnace.
[0123] The square pieces after grain boundary diffusion treatment were tested using a NIM-62000 permanent magnetic properties tester, and the results are shown in Table (2)
[0124] Table 2
[0125]
[0126] It can be seen from Table 2 that the increment of Hcj becomes smaller as the thickness of the product increases. However, under the condition of the same thickness, the increment of Hcj in Example 3 is higher than that in Comparative Example 3, which indicates that the Cu-Ga phase in the present invention utilizes its low melting point and wettability between grain boundaries to enhance the flow continuity between grain boundaries, thereby enhancing the diffusion depth of the grain boundary diffusion process and improving the demagnetization resistance of the sintered permanent magnet.
[0127] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A formula of a Zr-containing dual-high system sintered permanent magnet, characterized in that: Includes the following ingredients: RxT100-xy-zMyBz; Wherein, X, Y, and Z are the mass fractions of the corresponding elements, 28.5%≤X≤30.5%, 1%≤Y≤1.5%, and 0.86%≤Z≤0.96%; R is selected from one or more of Pr, Nd, Ce, Gd, Ho, Dy and Tb; M is Cu, Ga and Zr, and the content of Cu is 0.2%-0.45%, the content of Ga is 0.25%-0.55%, and the content of Zr is 0.3%-0.5%; T is Co and Fe, wherein 0.3%≤Co≤1.5%Co, and the remainder is Fe and impurities in the raw materials.
2. A Zr-containing dual-high system sintered permanent magnet formula according to claim 1, characterized in that: The content of Pr in the R is 6%-8%, the content of Nd is 22%-23.5%, the content of Dy is 0-1%, and the content of Tb is 0-0.6%.
3. A Zr-containing dual-high system sintered permanent magnet formula according to claim 1, characterized in that: The content of Cu in the M is 0.25%-0.45%, the content of Ga is 0.35%-0.55%, the content of Zr is 0.3%-0.5%, the content of Al is 0.03%-0.2%, the content of Co in the T is 0.3%-1.5%, and the content of B is 0.88%-0.93%.
4. A Zr-containing dual-high system sintered permanent magnet formula according to claim 1, characterized in that: The RxT100-xy-zMyBz includes PrNd 29%-30.5%, Co 0.5%, Cu 0.2%-0.45%, Ga 0.3%-0.55%, Zr 0.3%-0.5%, B 0.91%, Al 0.05% and the balance is Fe and impurities in the raw materials.
5. A method for manufacturing a Zr-containing dual-high system sintered permanent magnet, characterized in that: A Zr-containing dual-high system sintered permanent magnet formula for any one of claims 1 to 4 comprises the following steps: S1. Vacuum melting and hydrogen crushing: using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the formula composition design, using a vacuum melting furnace to make alloy flakes, and then the alloy flakes are subjected to hydrogen crushing treatment; S2, air jet mill: add a certain proportion of organic additives, stir and grind, add antioxidants after discharging, stir evenly and store in nitrogen; S3, orientation molding: Orientation molding is carried out in an orientation magnetic field when the oxygen content of the press is lower than 500ppm, and then vacuum packaging and cold isostatic pressing are carried out to achieve a densification effect; S4, vacuum sintering: placing the green body after cold isostatic pressing in a vacuum sintering furnace, and performing gradient sintering after vacuuming; S5, grain boundary diffusion and aging treatment: the sintered blank is made into a 30*30*5mm square piece and then subjected to grain boundary diffusion treatment, and then to aging treatment; S6. Performance test: The blank after aging treatment is sampled into D10*10 samples and tested using NIM-62000 permanent magnetic performance tester.
6. The method for manufacturing a Zr-containing dual-high system sintered permanent magnet according to claim 5, characterized in that: The processing temperature of the alloy sheet in S1 is within 1500° C., the thickness is 0.1-0.5 mm, the dehydrogenation temperature in the hydrogen cracking treatment is 520-580° C., and the hydrogen content of the coarse powder after dehydrogenation is 600-1500 ppm.
7. The method for manufacturing a Zr-containing dual-high system sintered permanent magnet according to claim 5, characterized in that: The proportion of organic additives in S2 is 0.12%, the proportion of antioxidants is 0.1%, the stirring time is 1.5 hours, the online particle size of the jet mill is D50: 3.8-4.3 μm, and the system oxygen supplementation is 30 ppm.
8. The method for manufacturing a Zr-containing dual-high system sintered permanent magnet according to claim 5, characterized in that: The orientation magnetic field strength in S3 is greater than 1.6 T. In the cold isostatic pressing treatment, the pressure is 160-220 MPa, and the holding time is 15-35 s.
9. The method for manufacturing a Zr-containing dual-high system sintered permanent magnet according to claim 5, characterized in that: The sintering temperature of the vacuum sintering in S4 is 1020-1120°C, the high temperature holding time is 4-12h, the vacuum degree is ≤0.5Pa, the aging treatment is multi-stage aging, including primary aging, secondary aging, and tertiary aging. The primary aging treatment temperature is 850°C-950°C, and the holding time is 1-3h. The secondary aging treatment temperature is 420°C-520°C, and the holding time is 3-10h. The tertiary aging treatment temperature is 550°C-650°C, and the holding time is 3-10h. The density of the sintered blank is >7.
5.
10. The method for manufacturing a Zr-containing dual-high system sintered permanent magnet according to claim 5, characterized in that: The diffusion source in the grain boundary diffusion in S5 includes terbium hydride, dysprosium hydride, terbium alloy, and dysprosium alloy. The grain boundary diffusion process includes one of screen printing, coating, and PVD. The grain boundary diffusion temperature is 820° C.-920° C., and the diffusion time is 10-30 hours.